The Implementation of the Independent Learning Curriculum in Indonesian Language Instruction to Foster Student Creativity - Riska Maulita Hasibuan; Ade Kusmana; Rustam Rustam (STAI Miftahul Ula Nganjuk, 2024)
This study aims to examine, describe, and analyze the implementation of the